Aproveitamento da biomassa residual urbana para síntese de bioetanol - Oliveira, Fabieli Aparecida de (2016)
The scarcity of fossil fuels and global environmental awareness make new energy alternatives are studied in order to develop clean energy technologies and this perspective renewable fuels are highlighted, including bioethanol or second-generation ethanol. Lignocellulosic biomass includes any plant material that provides energy to be processed, especially by the presence of cellulose and hemicellulose carbohydrate sources (pentoses and hexoses) which can be converted by acidic hydrolysis into fermentable sugars to produce ethanol . The production of fuels from biomass allows the use of acreages of waste and reduces competition for food crops. Furthermore, during the growth process of the plant absorbs carbon dioxide from the air while maintaining balanced levels of it in the atmosphere. Thus the use of urban forest residues (pruning) is to assist in air quality and the same time encourage the reuse of waste energy, reducing environmental impacts. Thus, through pruning of urban trees to investigate the potential for biofuel production in the municipality of Santa Helena-PR. For this, the collection of urban tree pruning samples was performed, drying at 60 ° C, grinding the same, followed by acid hydrolysis at concentrations of 1 and 5% H2SO4, pH adjustment and following fermentation with the microorganism Saccharomyces cerevisiae commercial use. For data analysis was used absorption spectrum in the near infrared, in the region from 1600 to 1800 nm and evaluation of sugars present in the sample by the degree brix and Fehling method. It was observed that the samples hydrolyzed at 1% and no hydrothermal treatment had a lower concentration of sugars and consequently ethanol production was low, less than 1% of ethanol produced, as compared with the 1% solutions hydrothermic treatment. The medium was efficient in the fermentation, since characteristic bands (1600-1800 nm) were identified in samples of the spectra. The cuttings were subjected to 42-mesh sieve showed increased release of sugars and consequently bioethanol. When compared the efficiency of hydrolysis, carried out with 5% acid it is more representative of both the release fermentable sugars, about 11%, and in ethanol. However, the amount of waste produced has a significant potential for the production of ethanol, reaching a production of 153.900 liters of ethanol during the months of June, July and August 2015. The prunings in carbohydrate content is significant and waste produced at process end can also be used, increasing its feasibility. Further studies aimed at improving the technique will help in increased production and process efficiency.